Environmentalism with Indonesian National Army: urban revitalization of the Citarum River in Karawang Regency, Indonesia - Widodo; Nandang Alamsah Deliarnoor; R. Widya Setiabudi Sumadinata; Novie Indrawati Sagita; Abdillah; Ana Fitriana Poerana; Luki Oka Prastio (Cogent Social Sciences, 2024)
This study aimed to examine the involvement of the Indonesian National Armed Forces (TNI) in the revitalization of the Citarum River through Military Operations Other Than War (OMSP) in Citarum Harum Program in Karawang Regency. A qualitative method was used with primary data obtained through direct observation, in-depth interviews, and secondary data from relevant literature and documents. Subsequently, the data were analyzed using Nvivo 12 Pro. The results of the research show that the substance of the policy content in Presidential Regulation of the Republic of Indonesia Number 15 of 2018 is very clear in the management of the Citaram River by involving the TN. The involvement of the Indonesian Army in the Citarum Harum Program had a significant impact on its success. The TNI has been able to optimize active participation in community and industrial empowerment through OMSP. In addition, their commitment and determination towards total revitalization has increased public and industrial awareness and compliance. The strength of this research lies in the approach to handling the Citarum River problem, through the Citarum Harum program. This study contributes to being used as material by the government and society in handling other environmental issues. The success of the Citarum Harum Program has contributed to the improvement of the Citarum River which can be used as a source of irrigation, hydroelectric power generation and tourism.